Non-line of Sight Transient Rendering - Royo Meneses, Diego; Garcia, Jorge; Muñoz, Adolfo; Jarabo, Adrián (Jornada de Jóvenes Investigadores del I3A, 2022)
Non-line of sight imaging reconstructs hidden geometry using time-resolved measurements of indirect diffuse reflections emitted by a laser. To help develop new applications, we simulate light transport in these occluded scenes and introduce a set of simple, yet effective subpath sampling techniques for efficiency, with an open-source implementation.